Efficient method for Agrobacterium-mediated genetic transformation of tobacco nodal segments - Silva, R. G. da [UNESP]; Coppede, J. S.; Silva, J. O. L.; Zingaretti, S. M. [UNESP] (Funpec-editora, 2018)
Plant transformation is a widely used procedure for obtaining transgenic plants and to develop plant models to understand gene function. Plant models such as Nicotiana tabacum are widely used for understanding gene responses to external influences. An important tool in such studies is genetic transformation through infection with Agrobacterium tumefaciens. However, this transformation is often inefficient. Consequently, development and optimization of techniques to promote high rates of seedling regeneration of transgenic tobacco is imperative. The methods tested for infection of tobacco explants consisted of injecting 10 mu l of the bacterial culture directly into anodal segment using an insulin syringe (1 mL); bacterial co-cultivation with nodal segments and micro-sectioned leaf disks. Infection through punctures made with a syringe in nodal segments of tobacco and no co-cultivation period was the most efficient in the regeneration process and in obtaining genetically transformed plants, with 88 and 75% success rates, respectively. We obtained an increase of 50% in the transformation rates when compared to previous studies using N. tabacum.
Keywords: Explant; Method; Regeneration; Transgenic